Tetrathia[7]helicene Phosphorus Derivatives: Experimental and Theoretical Investigations of Electronic Properties, and Preliminary Applications as Organocatalysts. Issue 4 (25th February 2016) - Dova, Davide; Viglianti, Lucia; Mussini, Patrizia R.; Prager, Stefan; Dreuw, Andreas; Voituriez, Arnaud; Licandro, Emanuela; Cauteruccio, Silvia
Abstract: Combined experimental and theoretical study on the electronic characteristics of tetrathiahelicene (7‐TH) alkyl and aryl phosphorus derivatives, including phosphanes, phosphine–borane complexes, phosphine oxides, and phosphine–selenides, is described. The collected data give useful information on the σ‐donor ability of the phosphorus atoms, which mainly depends on the aryl or alkyl nature of the substituents at the phosphorus atom. Electrochemical investigations provide the relationships between the electronic and structural properties, and quantum chemical calculations show a clear dominance of the 7‐TH scaffold on the electronic properties of all investigated molecules. Finally, different electronic and steric properties of 7‐TH phosphanes strongly influenced their catalytic behavior, for example, as Lewis base organocatalysts in typical [3+2] annulation reactions. Abstract : Tetrathiahelicene phosphorus derivatives : A deep investigation onto the electronic and electrochemical properties of tetrathiahelicene (7‐TH) alkyl and aryl phosphorus derivatives has been performed. The σ‐donor ability of the phosphorus atoms mainly depends on the aryl or alkyl nature of the substituent. Quantum chemical calculations show a clear dominance of the 7‐TH scaffold on the electronic properties of all investigated molecules.